FIRST FINDS OF THE GENUS OSWALDHEERIA.(MIRO\LACEAE, PINOPSIDA) IN THE LOWER CRETACEOUS OF NORTHERN ASIA - Nosova N.V. (My University, 2001)
Material of the genus Oswaldheeria (Miroviaceae, Pinopsida) from the Mesozoic of Russia is presented for the first time. A new species, Oswaldheeria orientalis, is described, and a new combination, Oswaldheeria neosibirica, is proposed.
Keywords: Oswaldheeria; Mesozoic; Russia; Mesozoic; Мезозой